Export Competitiveness in Indonesia's Manufacturing Sector - Winkler, Deborah; Farole, Thomas (World Bank, Jakarta, 2017)
The Indonesian manufacturing sector experienced a 'lost decade' in the aftermath of the Asian financial crisis. While many believe that the sector is now in inexorable decline, this note argues that there may be a 'second chance' for export manufacturing, given Indonesia's relative cost competitiveness, the rapidly growing domestic market, and the opportunities of integrating into value chains facilitated by new regional growth poles. Simply relying on these factors, however, may result in short-term growth but will ultimately lead back to stagnation. Instead, Indonesia must use this opportunity to make an aggressive effort to improve manufacturing sector competitiveness, including addressing traditional investment climate issues, but most importantly, weaknesses in the quality and innovation environment. It is through this that the Indonesian manufacturing sector will begin to move up the value chain, build deep and competitive domestic value chains, and deliver quality and sustainable job opportunities.